Engineered reclamation fill material created from excavated soft material and Granulated Blast Furnace Slag (GBFS) - Chew, Chia Weei. (2013)
This study presents the results of a treatability study for excavated soft soil stabilization using granulated blast furnace slag (GBFS) and lime for possible use in landfill. The excavated soft soil was silty, clayey sand obtained from the Land Transport Authority’s staging ground. The GBFS and lime were added in percentages of 25%, 24% and 0%, 1% by weight respectively.